2017
DOI: 10.3390/nano7090264
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Tunable Multiferroic Properties in Sol-Gel-Derived Nanocrystalline Sr(Ti1−xFex)O3−δ Thin Films

Abstract: Sr(Ti1−xFex)O3−δ (0 ≤ x ≤ 0.2) thin films were grown on Si(100) substrates with LaNiO3 buffer-layer by a sol-gel process. Influence of Fe substitution concentration on the structural, ferroelectric, and magnetic properties, as well as the leakage current behaviors of the Sr(Ti1−xFex)O3−δ thin films, were investigated by using the X-ray diffractometer (XRD), atomic force microscopy (AFM), the ferroelectric test system, and the vibrating sample magnetometer (VSM). After substituting a small amount of Ti ion with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
(67 reference statements)
1
15
0
Order By: Relevance
“…For these reasons, doping of BaTiO3 and CaTiO3 by Fe and Co, which results in bandgap narrowing and enhanced electron transfer, could exhibit improved electrocatalytic performance. Observations from this study were being agreed with the study reported by B. Sawicki et al and Y. Wang et al, which stated that lower bandgap improve the electrocatalytic activity [48][49].…”
Section: Electrocatalytic Activitysupporting
confidence: 92%
“…For these reasons, doping of BaTiO3 and CaTiO3 by Fe and Co, which results in bandgap narrowing and enhanced electron transfer, could exhibit improved electrocatalytic performance. Observations from this study were being agreed with the study reported by B. Sawicki et al and Y. Wang et al, which stated that lower bandgap improve the electrocatalytic activity [48][49].…”
Section: Electrocatalytic Activitysupporting
confidence: 92%
“…Owing to their immiscibility, the components are likely to segregate ensuing the formation of nonmagnetic matrix with small magnetic precipitates embedded in it [ 34 , 35 , 36 , 37 ]. After replacing a minor amount of Ti ion with Fe, extremely enhanced ferroelectric characteristics were obtained successfully, while the thin films were annealed in nitrogen, air, and oxygen atmospheres [ 38 ]. Thickness dependence, which is mainly due to deposition time or power variations of the magnetic hysteresis observed in NiFeAg heterogeneous alloy films at ambient temperature onto glass substrates [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the present case, it was observed that Fe 2p 3/2 and Fe 2p 1/2 correspond to B.Es ~ 712.6 eV and ~ 726.04 eV respectively. The Fe 2p 3/2 and Fe 2p 1/2 peaks shift towards higher energies as compared to typical binding energy of Fe 2+ and Fe 3+ oxidation states clearly indicating the existence of higher oxidation state (Fe 4+ ) constituting Fe 2p 27 31 . With regard to Bi, the Bi 4f XPS spectra shown in Fig.…”
Section: Resultsmentioning
confidence: 92%